Mnenje laične javnosti glede izvajanja ter plačevanja storitev farmacevtske skrbi v Sloveniji - Kos, Mitja (Farmacevtski vestnik, 2011)
Aim of the study was to assess the Slovenian public view on performance and willingness to pay for pharmaceutical care services. Questionnaires have been sent by mail to a random sample of Slovenian general population (age >= 18 years, N=1100). According to lay public view (response rate= 21%) the pharmaceutical care services in Slovenia have not yet been sufficiently implemented, although there is a high likelihood for use of such services. At the same time a pharmacist (M. Pharm.) is recognized as a competent expert that could upgrade services from current practice. Moreover, most elements of pharmaceutical care are recognized as a relative novelty among Slovenian community pharmacy services. Similar views were expressed by respondents towards the package of pharmaceutical care services, which at least some people are willing to pay either through direct payments (the proportion of respondents willing to pay was 22.6%, median was 30 EUR per year), or through increase of health insurance premium (the proportion of respondents willing topay was 37.1%, median of additional increase of premium was 6 EUR per month).
Keywords: ankete; farmacevtska skrb; laična javnost; Slovenia; Slovenija; storitve; vrednotenje